Dziennikarz versus specjalista ds. public relations – toksyczny związek czy małżeństwo z rozsądku? - Ossowski, Szymon (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2009)
It is impossible to sum up the character of mutual relations between journalists and PR specialists, who frequently act as spokesmen, in a single statement. These relations are multidimensional and have both positive and negative aspects. Both parties voice their opinions on each other, some justified, other grossly exaggerated. Both parties commit sins, but they also have a very important role to play. Journalists should serve society, and on behalf of this society they should exercise control over public authorities. Journalists are mainly supposed to provide their recipients with reliable and true information. PR specialists are also supposed to provide information, yet that concern th business. Public opinion and its role in the liberal-democratic political system are of crucial significance this relation. Both parties want to mold public opinion, to win its interest, they both function thanks to it and depend on it. They are also indispensably related, as evidenced by both the theory and practice of ther relations, which also necessitates that care is taken their appropriate quality.